Embedding Theorems for the Dunkl Harmonic Oscillator on the Line - Álvarez López, J.A.; Calaza, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
Embedding results of Sobolev type are proved for the Dunkl harmonic oscillator on the line.